SIMPLEX METHOD APPLICATIONS USING C LANGUAGE - Boby Iskandar; Diyah Ruri Irawati, Skom., MMSI (Jurnal Sistem Informasi, 2005)
Abstract:Simplex method is one of the techniques of linear programming that can be used asan alternative to determine the allocation of limited resources among severalcompeting activities to achieve a desired goals and objectives optimally, such as theone of which is to maximize profits. Linear programming problems related to theproblem of finding the optimum values (maximum / minimum) the best from anobjective function with constraints that exist.Simplex method of calculation is based on the iteration process, starting with theinitial solution is continuously improved in order to obtain optimal solutions.Solutions said to be optimal if no basic values than variables can not be enlargedagain to raise the value of the objective function without violating existingconstraints. In the simplex method, pour into a programming language, the authorschose the C language as the language used, because the C language has a high levelof mathematical calculations and compiled to process faster than any other languagewith a writing style that is easily understood.